Utilization of Avocado Leaves (Persea americana Mill) Ethanol Extract in Acne Spot Gel Formulation - Hidayati, Nurul; Amanda, Putri Fadillah; Setiawansyah, Arif (Indonesian Journal of Cosmetics, 2024)
Avocado leaves (Persea americana Mill) are classified as a type of herbal plant that has many benefits and can be used as traditional medicine. The components in avocado leaves that have antibacterial properties are flavonoids, saponins, and tannins. To increase public interest in utilizing avocado leaves, the development of a formulation in the form of acne spot gel from avocado leaf ethanol extract can be undertaken. The base used in this study is carbopol 934, the base that commonly used in gel production. The purpose of this study is to determine the effect of variations in the concentration of avocado leaf ethanol extract on the physical properties of acne spot gel. The extract was obtained by macerated 50.06 grams of avocado leaves (yield 25.03%). The formulation was produced in gel form with four formulas that had variations in the concentration of ethanol extract, those are formula 0 (0%), formula 1 (5%), formula 2 (10%), and formula 3 (15%). The acne spot gel was subjected to physical property tests including organoleptic, pH, spreadability, and adhesion. All tested formulas met the quality requirements of the acne spot gel formulation. The evaluation data were analyzed using One-Way ANOVA to determine significant differences. Based on the evaluation results, the variation in ethanol extract concentration had a significant effect (p < 0.05) on adhesion, where higher concentrations of ethanol extract could increase the adhesion of the formulation.